Strategia czystszej produkcji elementem konkurencyjności przedsiębiorstw - Burzyńska, Dorota (Clean Production Strategy as A Component Of Companies' Competitiveness, 2008)
Implementation of modern strategies as clean production for environmental managing is not only an evidence of increasing companies ecological consciousness but also an element of competitive struggle. Taking into account changes which take place in social consciousness and increasing acceptance for clean natural environment as components of social and individual welfare, enterprises must build their competitive advantages through product diversification and respect of ecological preferences of groups of consumers. One should expect that correct implementation of clean production may be an instrument supporting economic growth, increasing raw materials and energy managing efficiency, stimulating innovativeness through permanent searching for new, better, more efficient and cheaper methods of production. Introduction of modern technologies may be an instrument which creates favourable conditions for competitiveness because of decreasing costs of environment pollution and as final result competitive prices of commodities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 77-83